Water at the forefront of one health in Ethiopia - Mateo-Sagasta, Javier; Haile, Alemseged Tamiru; Beza, Habtamu Mulat (International Water Management Institute, 2024)
In Ethiopia, where the Blue Nile begins its journey, water is not just a resource—it’s a lifeline. It nourishes crops, quenches thirst and sustains livelihoods. But until recently, water was notably absent from the nation’s One Health planning and committees, where human, animal, and environmental health converge to address complex health challenges. That is until Ethiopia’s Water Champions stepped forward to ensure that water takes its rightful place at the center of One Health.